Surgical masks vs respirators for the protection against coronavirus infection: state of the art - Violante, Tommaso; Violante, Francesco Saverio (La Medicina del Lavoro, 2020)
Background: During the Covid-19 outbreak, a recurrent subject in scientific literature has been brought back into discussion: whether surgical masks provide a sufficient protection against airborne SARS-CoV-2 infections. Objectives: The objective of this review is to summarize the available studies which have compared the respective effectiveness of surgical masks and filtering facepiece respirators for the prevention of infections caused by viruses that are transmitted by the respiratory tract. Methods: The relevant scientific literature was identified by querying the PubMed database with a combination of search strings. The narrower search string “(surgical mask *) AND (respirator OR respirators)” included all the relevant articles retrieved using broader search strategies. Of all the relevant articles found, seven systematic reviews were selected and examined. Results: The currently available scientific evidence seems to suggest that surgical masks and N95 respirators/FFP2 confer an equivalent degree of protection against airborne viral infections. Discussion: Since surgical masks are less expensive than N95 respirators but seem to be as effective in protecting against airborne infection and they are also more comfortable for the user, requiring less respiratory work, they should be the standard protective device for health care workers and especially for workers who carry out non-medical jobs. Filtering facepiece respirators, whose extended use is less comfortable for the wearer, may be preferred for procedures which require greater protection for a shorter time.